Odpowiedzi

2010-01-18T20:33:28+01:00
6+1 / x+ 1 = 2/x+1
7 /x+1 = 2 / x+1
7 : x+ 1 = 2 : x +1
7-2=x+1-x+1
5=2x-2
5=x
2010-01-18T20:46:25+01:00
6+1/x+1(w ułamku)=-2/x+1(w ułamku)
(6+1):(x+1)=-2:(x+1)
(6+1)*(1/x w ułamku -1)=-2*(1/x w ułamku -1)
6/x(w ułamku)-6+1/x(w ułamku)-1=2/x(w ułamku)-2
6/x(w ułamku)+1/x(w ułamku)-2/x(w ułamku)=6+1-2
5/x(w ułamku)=5 /*x
5/x(w ułamku)*x=5*x
5x=5 /:5
x=1
2010-01-18T20:47:53+01:00
6 + 1/x +1 = -2/x +1
6 + 1/x =-2/x }*x
6+1/x *x/1=-2/x * x/1
7=-2
Odp. Nie ma rozwiazanie